Aversion for Avulsion: A Case of Delayed Diagnosis of Traumatic Tricuspid Rupture - Wendy K. Bernstein; Nicholas Goehner (Case Reports in Anesthesiology)
Tricuspid rupture secondary to blunt force trauma is a rare diagnosis. However, the incidence of this injury is rising due to the improved initial treatment of complex trauma patients as well as enhanced early detection methods through the use of cardiac ultrasound. We report the case of an otherwise healthy 42 year old male who sustained significant blunt force trauma after a single motor vehicle accident. The diagnosis of traumatic papillary rupture and disruption of the valve apparatus was made on the day of admission after perioperative hemodynamic compromise and the use of intraoperative transesophageal echocardiography. However, treatment was delayed due to concerns of systemic anticoagulation leading to his eventual demise.